1982
DOI: 10.1111/j.1528-1157.1982.tb06197.x
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma, Toxocara, and Epilepsy

Abstract: The presence of positive antibody titres to Toxoplasma and Toxocara in an adult epileptic population has been examined in relation to other observations of aetiological importance. With Toxoplasma, and more particularly with Toxocara, a higher incidence of positive antibody titres was recorded than in nonepileptic populations. Comparison with previous studies in childhood epilepsy indicate that the incidence of positive titres increased with age throughout adult life. Despite attention to the age of onset of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 15 publications
0
30
0
1
Order By: Relevance
“…Early reports have suggested that people with epilepsy (PWE) have a high rate of exposure to T. canis (155,156). Woodruff et al (155) found that a higher percentage of PWE (7.5%) reacted positively to a toxocariasis skin test than the case for apparently healthy controls (2.1%).…”
Section: Seizurementioning
confidence: 99%
“…Early reports have suggested that people with epilepsy (PWE) have a high rate of exposure to T. canis (155,156). Woodruff et al (155) found that a higher percentage of PWE (7.5%) reacted positively to a toxocariasis skin test than the case for apparently healthy controls (2.1%).…”
Section: Seizurementioning
confidence: 99%
“…T. canis has been suggested as an environmental risk factor for asthma among some inner-city populations (42). Similarly, in the brain, T. canis has been implicated as one of the causes of so-called idiopathic seizure disorders (9), as well as a cause of functional intestinal disorders (25). One study implicated Toxocara as a contributing factor in skin disorders of at least two varieties (prurigo and urticaria) (22), while another presented indirect evidence linking Toxocara infection with a form of eosinophilic arthritis (45).…”
Section: Vlmmentioning
confidence: 99%
“…Toxocara may represent a co-factor in idiopathic seizures (Critchley et al, 1982), and especially in partial epilepsy (Nicoletti et al, 2007). The presence of granulomas in the brain has been suggested to elicit focal seizures (Critchley et al, 1982). Research to verify increased risk of cognitive deficits in infected children has remained inconclusive (Jarosz et al, 2010).…”
Section: Laboratory Diagnosis Clinical Spectrum and Treatment Of Hummentioning
confidence: 99%
“…Central nervous system involvement in VLM has been associated with epilepsy (Woodruff et al, 1966), behavioral changes and cognitive deficits. Toxocara may represent a co-factor in idiopathic seizures (Critchley et al, 1982), and especially in partial epilepsy (Nicoletti et al, 2007). The presence of granulomas in the brain has been suggested to elicit focal seizures (Critchley et al, 1982).…”
Section: Laboratory Diagnosis Clinical Spectrum and Treatment Of Hummentioning
confidence: 99%